2018
DOI: 10.1002/jcp.27260
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA–antisense noncoding RNA in the INK4 locus accelerates wound healing in diabetes by promoting lymphangiogenesis via regulating miR‐181a/Prox1 axis

Abstract: Background: Slow lymphangiogenesis is one crucial reason for the impaired wound healing process in diabetes. Accumulative evidence showed that long noncoding RNA-antisense noncoding RNA in the INK4 locus (ANRIL) could influence lymphangiogenesis. Besides, miR-181a has been reported to regulate Prox1 that is essential for lymphangiogenesis. However, the relationship between ANRIL and miR-181a as well as the definitive function of ANRIL in lymphangiogenesis is not clear.Methods: The diabetic mouse model was set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 37 publications
5
24
0
Order By: Relevance
“…It was demonstrated in the present study that ANRIL upregulated SIRT1 by sponging miR-181a, thus identifying another ANRIL target. Remarkably, two recent investigations reinforce the present data by also documenting that ANRIL inhibits cell senescence of vascular smooth muscle cells ( 29 ) and promotes lymphangiogenesis ( 30 ) by regulating miR-181a. In conjunction with these previous studies, the present results suggested that the negative regulation of miR-181a by ANRIL may be a critical mechanism by which ANRIL exerts its versatile activities.…”
Section: Discussionsupporting
confidence: 89%
“…It was demonstrated in the present study that ANRIL upregulated SIRT1 by sponging miR-181a, thus identifying another ANRIL target. Remarkably, two recent investigations reinforce the present data by also documenting that ANRIL inhibits cell senescence of vascular smooth muscle cells ( 29 ) and promotes lymphangiogenesis ( 30 ) by regulating miR-181a. In conjunction with these previous studies, the present results suggested that the negative regulation of miR-181a by ANRIL may be a critical mechanism by which ANRIL exerts its versatile activities.…”
Section: Discussionsupporting
confidence: 89%
“…LncRNAs play a key role in the regulation of target genes in many diseases (Wu et al 2018, Cremer et al 2018. Furthermore, antisense lncRNAs can regulate target gene expression via a range of different mechanisms (Villegas & Zaphiropoulos 2015, He et al 2019. In the present study, our group showed that AC002454.1 may be one of the molecular targets involved in the origin of eutopic endometrial change in EMS.…”
Section: Discussionsupporting
confidence: 48%
“…Our results suggested that H19 could directly target miR-152-3p and repressed the expression of miR-152-3p. Many reports about the mechanism of lncRNA sponge showed that the expression of miRNA was negatively regulated after overexpression or knockdown of lncRNA (34)(35)(36), but the specific mechanism of reducing the level of miRNA by the lncRNA sponge was not described in detail. However, a previous study demonstrated that HSURs, as a noncoding RNA, could interact with miR-27 in virally transformed T cells and dramatically decreased the level of miR-27 by directing degradation of mature miR-27 in a binding-dependent manner (37).…”
Section: Discussionmentioning
confidence: 99%